쇄골하동맥 혈전증에서의 MDCT 혈관조영술의 3D 영상 - 권대철; Dae Cheol Kweon (한국방사선학회 논문지, 2018)
MDCT의 3D 유용성을 입증하기 위해 쇄골하 혈전증을 수반한 73세 남자 환자를 대상으로 MIP, 볼륨렌더링, MPR의 3D 영상을 획득하여 쇄골하동맥의 혈전증을 명확하게 탐지하고 위치를 확인하여 임상에서 기초자료를 제공하여 환자의 진단 및 치료에 적용하고자한다. 스캔 데이터를 3차원 CT영상인 MIP, 볼륨렌더링, curve multiplanar reformation (MPR), virtual endoscopy 영상을 획득하였다. CT검사 환자의 데이터를 3D 프로그램으로 전송한 영상에서 3D 프로그램에서 측정한 상행대동맥은 364.28 HU, 좌총경동맥 413.77 HU, 좌쇄골하동맥 15.72 HU로 낮게 산출되었다. MIP coronal 영상으로 좌측의 쇄골하동맥의 혈전으로 폐쇄를 정확하게 보여주고 있다. 볼륨렌더링 3차원 영상으로 투과도 100%, 87-1265 HU를 적용하여 쇄골하동맥과 뼈를 동시에 묘출하고 있으며, 좌측 쇄골하동맥의 폐쇄 영상을 선명하게 보여주었으며 coronal curved MPR 및 sagittal curved MPR 영상으로 혈전의 의한 쇄골하동맥의 폐쇄를 3D 영상 처리 기능을 이용하여 정확하게 묘출하고 있다. 혈전에 의한 쇄골하동맥 폐쇄 증상 환자를 MDCT로 스캔하여 3D 영상 기법을 응용하여 쇄골하동맥의 폐쇄를 확인할 수 있어 임상에서 3D 기법을 응용하여 적절하게 진단에 적용할 수 있다. To demonstrate the 3D usefulness of MDCT, a 73-year-old male patient with subclavian thrombosis was obtained 3D images of maximum intensity projection (MIP), volume rendering, and multiplanar reformation (MPR) to clearly detect and locate the subclavian artery. The data will be provided to the patient for diagnosis and treatment. The scan data were acquired as 3D CT images MIP, volume rendering, curved MPR, and virtual endoscopy images. In the 3D program, the ascending aorta was measured as 364.28 HU, the left carotid artery was 413.77 HU, and the left subclavian artery was 15.72 HU. MIP coronal image shows the closure of the subclavian artery in the left side. Three-dimensional volume images were obtained with 100% permeability and 87-1265 HU. The coronal curved MPR and sagittal curved MPR images show the closure of the subclavian artery due to thrombus using 3D image processing. In the case of subclavian arterial occlusion due to thrombosis, the patient is scanned with MDCT and 3D image processing can be used to confirm occlusion of subclavian artery.